2016
DOI: 10.1038/npp.2016.101
|View full text |Cite
|
Sign up to set email alerts
|

The α7 Nicotinic Agonist ABT-126 in the Treatment of Cognitive Impairment Associated with Schizophrenia in Nonsmokers: Results from a Randomized Controlled Phase 2b Study

Abstract: A double-blind, placebo-controlled, parallel-group, 24-week, multicenter trial was conducted to evaluate the efficacy and safety of 3 doses of ABT-126, an α7 nicotinic receptor agonist, for the treatment of cognitive impairment in nonsmoking subjects with schizophrenia. Clinically stable subjects were randomized in 2 stages: placebo, ABT-126 25 mg, 50 mg or 75 mg once daily (stage 1) and placebo or ABT-126 50 mg (stage 2). The primary analysis was the change from baseline to week 12 on the MATRICS Consensus Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…Since galantamine does not act selectively through positive allosteric modulation of the α4β2 and α7 nicotinic receptors, it may not have been an optimal choice to test the potential utility of the α7 nicotinic receptor target. However, other recent studies with α7 nicotinic receptor partial agonists or agonists have failed to demonstrate efficacy for cognitive impairments 56,57 . Although these results are discouraging for the α7 nicotinic receptor target, no studies have examined the efficacy of a pure positive allosteric modulator of this receptor.…”
Section: Discussionmentioning
confidence: 98%
“…Since galantamine does not act selectively through positive allosteric modulation of the α4β2 and α7 nicotinic receptors, it may not have been an optimal choice to test the potential utility of the α7 nicotinic receptor target. However, other recent studies with α7 nicotinic receptor partial agonists or agonists have failed to demonstrate efficacy for cognitive impairments 56,57 . Although these results are discouraging for the α7 nicotinic receptor target, no studies have examined the efficacy of a pure positive allosteric modulator of this receptor.…”
Section: Discussionmentioning
confidence: 98%
“…There has been much a more substantial effort in the domain of α-7 receptor agonists; however, results have been inconsistent. Several different treatments have failed to show differences from placebo in studies on patients with schizophrenia ( 65 , 66 ). A short-term study of the α-7 receptor agonist DMXB-A found separation between active and placebo treatment in a cross-over design ( 67 ).…”
Section: Procholinergic Treatments For Augmentation Of Skills Traininmentioning
confidence: 99%
“…In another phase 2a trial in subjects with schizophrenia, ABT-126 demonstrated a precognitive effect in nonsmoking subjects, particularly in verbal learning, working memory, and attention (Haig et al, 2016b). A follow-up dose-ranging study showed that ABT-126 did not demonstrate a consistent effect on cognition in nonsmoking subjects with schizophrenia; however, a trend toward a therapeutic effect was observed on negative symptoms (Haig et al, 2016a).…”
Section: Introductionmentioning
confidence: 98%